Title:the importance of psychological counseling on academic achievement (study with high school students). - Hadjadj , Saad; Berkat, Hocine (sports creativity, 2025)
the object of the study is to identify the importance of psychological counseling on academic success, in the form of counseling services psychological represented in the provision of aspects(academic, social and psychological),and we also used the experimental approach, so that the research community included 180 students in the sports high school , in the capital of Algeria, and its sample was deliberately chosen, it included the 34 students of the Experimental Sciences ,as for the questionnaires and the program, they were approved and distributed after being judged by specialists and experts. Scores on the scales were statistically positive, indicating that there is a correlation between the variables and the problem research data highlighted applied to the sample, analyze using SPSS , As a general result, we have come to "a positive importance of the process of psychological counseling on academic success, a study in the sports high school